1977
DOI: 10.1111/j.1744-6570.1977.tb02089.x
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFYING DETERMINANTS OF RETENTION DECISIONS1

Abstract: Variables from five domains—demography, social background, service history, satisfaction, and performance—were used in a discriminant analysis approach to distinguishing three groups of naval personnel: Those eligible to reenlist who do, those eligible who do not, and those not eligible. Discriminant weights were derived from a sample of 642 first‐term enlisted men and cross‐validated on a sample of 628. The results indicated that both pre‐service characteristics (demography and social background) and in‐servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Other tests examining general knowledge have also been associated with attrition, individuals scoring lower on the Navy General Classification Test (GCT) were at much higher first-term attrition risk than those scoring higher (153,200). McCraw and Bearden (173) found that recruits in Air Force Technical Training reporting to the mental health clinic were 2.1 times more likely to be discharged if their Intelligence Quotient was below 100 compared to above 116.…”
Section: B Cognitive/psychosociai Factors (1) Armed Forces Qualificamentioning
confidence: 99%
See 4 more Smart Citations
“…Other tests examining general knowledge have also been associated with attrition, individuals scoring lower on the Navy General Classification Test (GCT) were at much higher first-term attrition risk than those scoring higher (153,200). McCraw and Bearden (173) found that recruits in Air Force Technical Training reporting to the mental health clinic were 2.1 times more likely to be discharged if their Intelligence Quotient was below 100 compared to above 116.…”
Section: B Cognitive/psychosociai Factors (1) Armed Forces Qualificamentioning
confidence: 99%
“…Most studies show that service members who are married or have dependents are more likely to exit the service before completion of their enlistment contracts when compared to non-married service members (61,64,67,70,82,114,150,153,172). The higher first-term attrition among married service members is independent of age, gender, or race with one exception: married and single Black women have similar first-term attrition (70).…”
Section: (5) Marital Status and Dependentsmentioning
confidence: 99%
See 3 more Smart Citations